Sentiment Analysis of the Song Lost - Bring Me the Horizon Based on Reviews on YouTube Using the SVM Algorithm - Efraim Moningkey; Wanki Dwi Warsun Sombo (Newinera Publisher, 2026)
Bring Me The Horizon's song